Pulmonary embolism: adherence to diagnostic protocol and prognostic markers - Kauppi, Juha (fi=Turun yliopisto|en=University of Turku|, 2026)
The aim of this study was to comprehensively evaluate the adherence to an externally validated diagnostic pulmonary embolism (PE) protocol. In addition, the long-term prognostic value of biomarkers such as N-terminal pro-B-type natriuretic peptide (NT-proBNP), C-reactive protein (CRP), D-dimer and cardiac troponin T (cTnT) were assessed in patients undergoing computed tomography pulmonary angiography (CTPA) for a suspected PE. Furthermore, this study analyzed the predictive performance of CTPA-derived markers of right ventricular (RV) dysfunction, including contrast agent (CA) reflux, for determining early mortality risk. In total 1001 patients suspected of PE underwent CTPA in the emergency department (ED) in this retrospective study, of whom 22.2% of patients had PE. Firstly, this study found that CTPA was frequently performed even in patients with low to intermediate pre-test probability without D-dimer testing. Secondly, biomarker profiles demonstrated prognostic significance: in confirmed PE, elevated NT-proBNP (>1000ng/L) and CRP (>50mg/L) predicted poor long-term survival, whereas in patients without PE, increases in multiple biomarkers (NT-proBNP, CRP, D-dimer, cTnT) were associated with worse outcomes. Finally, CA reflux into inferior vena cava (IVC) observed in CTPA and elevated NT-proBNP levels emerged as a potential early markers of poor prognosis in PE. These results emphasize the need for consistent use of validated risk scores and D-dimer testing to reduce unnecessary imaging. Furthermore, RV dysfunction markers in CTPA and biomarker assessment could help identifying patients at higher risk for adverse outcomes. KEYWORDS: Pulmonary embolism; CTPA; contrast agent reflux; biomarkers, prognosis

Tutkimuksen ensimmäisenä tavoitteena oli arvioida diagnostisten hoito-ohjeiden noudattamista keuhkoemboliaepäilyissä. Erityisesti tarkasteltiin keuhkojen varjoainetehosteisen viipalekuvauksen käyttöä suhteessa potilaiden keuhkoembolian ennakkotodennäköisyyteen ja D-dimeeri-testauksen suosituksiin sekä erilaisten biomerkkiaineiden hyötyä potilaan ennustearvioinnissa. Lisäksi arvioitiin, miten tietokonetomografisissa keuhkoangiografioissa (CTPA) (engl. computed tomography pulmonary angiography) todettavat sydämen oikean puolen kuormitusmuutokset vaikuttavat keuhkoemboliapotilaiden ennusteeseen. Tässä retrospektiivisessä tutkimuksessa analysoitiin 1001 päivystyspoliklinikan potilasta, joille oli tehty CTPA-tutkimus keuhkoemboliaepäilyn takia. Heistä 22,2 prosentilla todettiin keuhkoembolia. Tutkimuksessa havaittiin, että hoito-ohjeiden vastaisesti D-dimeeri-testi jäi usein ottamatta, ja että CTPA-tutkimus tehtiin tarpeettomasti matalan ja keskisuuren keuhkoemboliariskin omaavilta potilailta. Lisäksi tutkimuksessa todettiin ennustearvoa eri biomarkkereilla: keuhkoemboliapotilailla kohonnut NT-proBNP (>1000ng/L) ja CRP (>50mg/L) ennustivat heikompaa pitkän aikavälin selviytymistä, kun taas potilailla, joilla keuhkoemboliaa ei ollut, useiden biomarkkereiden kohoaminen liittyi huonompaan ennusteeseen. Lisäksi CTPA:ssa havaittu varjoaineen takaisinvirtaus alaonttolaskimoon sekä NT-proBNP arvojen kasvu nousivat esiin mahdollisena varhaisen huonon ennusteen merkkinä. Tulokset korostavat systemaattisen riskinarvion ja D-dimeeri tutkimisen merkitystä tarpeettoman kuvantamisen vähentämiseksi sekä biomarkkereiden ja kuvantamislöydösten hyödyntämistä kliinisessä päätöksenteossa ja seurannassa. AVAINSANAT: Keuhkoembolia; CTPA; varjoaine; biomarkkerit; ennuste